Charge-Transfer Complex of Linifanib with 2,3-dichloro-3,5-dicyano-1,4-benzoquinone: Synthesis, Spectroscopic Characterization, Computational Molecular Modelling and Application in the Development of Novel 96-microwell Spectrophotometric Assay - Darwish IA; Khalil NY; Alsaif NA; Herqash RN; Sayed AYA; Abdel-Rahman HM (Dove Medical Press, 2021)
Ibrahim A Darwish,1 Nasr Y Khalil,1 Nawaf A Alsaif,1 Rashed N Herqash,2 Ahmed YA Sayed,1 Hamdy M Abdel-Rahman3,4 1Department of Pharmaceutical Chemistry, College of Pharmacy, King Saud University, Riyadh, 11451, Saudi Arabia; 2Medicinal Aromatic and Poisonous Plant Research Centre, College of Pharmacy, King Saud University, Riyadh, 11451, Saudi Arabia; 3Department of Medicinal Chemistry, Faculty of Pharmacy, Assiut University, Assiut, 71526, Egypt; 4Department of Medicinal Chemistry, College of Pharmacy, Nahda University, Banisuef, EgyptCorrespondence: Ibrahim A DarwishDepartment of Pharmaceutical Chemistry, College of Pharmacy, King Saud University, PO Box 2457, Riyadh, 11451, Saudi ArabiaTel +966 114677348Fax +966 114676220Email idarwish@ksu.edu.saBackground: Linifanib (LFB) is a multi‐targeted receptor tyrosine kinase inhibitor used in the treatment of hepatocellular carcinoma and other types of cancer. The charge-transfer (CT) interaction of LFB is important in studying its receptor binding mechanisms and useful in the development of a reliable CT-based spectrophotometric assay for LFB in its pharmaceutical formulation to assure its therapeutic benefits.Purpose: The aim of this study was to investigate the CT reaction of LFB with 2,3-dichloro-3,5-dicyano-1,4-benzoquinone (DDQ) and its application in the development of a novel 96-microwell spectrophotometric assay for LFB.Methods: The reaction was investigated, its conditions were optimized, the physicochemical and constants of the CT complex and stoichiometric ratio of the complex were determined. The solid-state LFB-DDQ complex was synthesized and its structure was analyzed by UV-visible, FT-IR, and 1H-NMR spectroscopic techniques, and also by the computational molecular modeling. The reaction was employed in the development of a novel 96-microwell spectrophotometric assay for LFB.Results: The reaction resulted in the formation of a red-colored product, and the spectrophotometric investigations confirmed that the reaction had a CT nature. The molar absorptivity of the complex was linearly correlated with the dielectric constant and polarity index of the solvent; the correlation coefficients were 0.9526 and 0.9459, respectively. The stoichiometric ratio of LFB:DDQ was 1:2. The spectroscopic and computational data confirmed the sites of interaction on the LFB molecule, and accordingly, the reaction mechanism was postulated. The reaction was utilized in the development of the first 96-microwell spectrophotometric assay for LFB. The assay limits of detection and quantitation were 1.31 and 3.96 μg/well, respectively. The assay was successfully applied to the analysis of LFB in its bulk and tablets with high accuracy and precision.Conclusion: The assay is simple, rapid, accurate, eco-friendly as it consumes low volumes of organic solvent, and has high analysis throughput.Keywords: linifanib, 2,3-dichloro-3,5-dicyano-1,4-benzoquinone, charge-transfer reaction, spectroscopic techniques, 96-microwell spectrophotometric assay, high-throughput pharmaceutical analysis